Transcriptional Landscape of Vero E6 Cells during Early Swine Acute Diarrhea Syndrome Coronavirus Infection - Siying Zeng; Ouyang Peng; Ruipu Sun; Qiuping Xu; Fangyu Hu; Yan Zhao; Chunyi Xue; Yongchang Cao; Hao Zhang (Viruses, 2021)
Swine acute diarrhea syndrome coronavirus (SADS-CoV) is a newly emerged and highly pathogenic virus that is associated with fatal diarrhea disease in piglets, causing significant economic losses to the pig industry. At present, the research on the pathogenicity and molecular mechanisms of host-virus interactions of SADS-CoV are limited and remain poorly understood. Here, we investigated the global gene expression profiles of SADS-CoV-infected Vero E6 cells at 12, 18, and 24 h post-infection (hpi) using the RNA-sequencing. As a result, a total of 3324 differentially expressed genes (DEG) were identified, most of which showed a down-regulated expression pattern. Functional enrichment analyses indicated that the DEGs are mainly involved in signal transduction, cellular transcription, immune and inflammatory response, and autophagy. Collectively, our results provide insights into the changes in the cellular transcriptome during early infection of SADS-CoV and may provide information for further study of molecular mechanisms.